Dysregulated Mitochondrial Dynamics and Metabolism in Obesity, Diabetes, and Cancer - Dai, Wenting; Jiang, Lei (Frontiers in Endocrinology, 2019)
Metabolism describes the life-sustaining chemical reactions in organisms that provide both energy and building blocks for cellular survival and proliferation. Dysregulated metabolism leads to many life-threatening diseases including obesity, diabetes and cancer. Mitochondria, subcellular organelles, contain the central energy-producing metabolic pathway, the tricarboxylic acid (TCA) cycle. Also, mitochondria exist in a dynamic network orchestrated by extracellular nutrient levels and intracellular energy needs. Upon stimulation, mitochondria undergo consistent inter-change through fusion (small to big) and fission (big to small) processes. Mitochondrial fusion is primarily controlled by three GTPases: mitofusin 1 (Mfn1), Mfn2, and optic atrophy 1 (Opa1); while mitochondrial fission is primarily regulated by GTPase dynamin-related protein 1 (Drp1). Dysregulated activity of these GTPases results in disrupted mitochondrial dynamics and cellular metabolism. This review will update the metabolic roles of these GTPases in obesity, diabetes and cancer.